Determination of IL-6, TNF-Î± and VEGF levels in the serums of patients with colorectal cancer - Coşkun, í–.; í–ztopuz, í–.; í–zkan, í–. F. (Cellular and Molecular Biology, 2017)
Cytokines are multifunctional polypeptides synthesized by different body cells. They have clinical significance in terms of disease diagnosis, treatment and prevention. Cytokines TNF-Î± and IL-6 play an important role in the growth and differentiation of cells.Vascular Endothelial Growth Factor (VEGF) is excessively produced in epithelial, mesenchymal, and particularly in tumor cells. Studies have shown that the increased serum concentrations of IL-6, TNF-Î±, VEGF are strongly associated with colorectal cancer and directly with the clinical stage of the disease. This can be used to diagnose cancer and to identify patients with a bad prognosis who can avail themselves of a more aggressive treatment. The present study investigated the role of cytokines in the development of cancer by comparing preoperative serum cytokine levels of patients suffering from colorectal cancer with those of the healthy control group. The prognostic significance of the data obtained has also been evaluated. For this purpose, IL-6, TNF-Î± and VEGF levels in 60 serums, 30 preoperatively taken from patients with colorectal cancer and 30 from a healthy control group at í‡anakkale Onsekiz Mart University General Surgery Clinic, were determined by ELISA kits. The statistical analyses of the obtained data were evaluated on SPSS, a statistical package program. In this study, no significant difference was obtained between the mean scores concerning the IL-6 and VEGF serums of the colorectal cancer and healthy group (p>.05). But a statistically significant decrease was observed in the TNF-Î± serum level of the colorectal cancer group in comparison with the control group (p= .016; p < .05).